Heat and Mass Transfer in Fires: Scaling Laws and their Application - Torero, Jose L (My University, 2005)
Fire is a phenomenon that covers a multiplicity of scales depending on the different processes involved. Length scales range from the nanometres when addressing material flammability to the kilometres when dealing with forest fires, while time scales cover a broad spectrum too. Heating of structural elements can be measured in hours while characteristic chemical times for reactions do not exceed the millisecond. Despite these wide ranges, a series of simple scaling laws seem to describe well a multiplicity of processes associated to fire. In this review some of those laws will be presented covering a wide range of events, from ignition to compartment fires and global building behaviour. Different non-dimensional parameters will be generated and placed in the context of heir engineering applications.
Keywords: forest; wildfire; non-dimensional; laws